The generalized kinetic equation for symmetric particle systems - Hubal, Halyna M. (Mathematica Scandinavica, 2012)
The generalized kinetic equation is obtained for symmetric system of many particles interacting via a pair potential. A representation of a solution of the Cauchy problem for the BBGKY hierarchy is used in the form of an expansion over particle groups whose evolution is governed by the cumulants (semi-invariants).